2002
DOI: 10.1001/archinte.162.16.1885
|View full text |Cite
|
Sign up to set email alerts
|

A Utilization Management Intervention to Reduce Unnecessary Testing in the Coronary Care Unit

Abstract: The utilization management intervention was associated with significant reductions in test ordering without a measurable change in clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 15 publications
0
70
0
5
Order By: Relevance
“…Various interventions like education, guideline management and computer model have been practiced to reduce the laboratory utilization. Wang et al [8] demonstrated the modest reduction in routine testing after development of guideline, order template design and education. Computer based model reminding the physician about the redundant laboratory test has been effective to some extent to reduce the number of test performed [9].…”
Section: Discussionmentioning
confidence: 99%
“…Various interventions like education, guideline management and computer model have been practiced to reduce the laboratory utilization. Wang et al [8] demonstrated the modest reduction in routine testing after development of guideline, order template design and education. Computer based model reminding the physician about the redundant laboratory test has been effective to some extent to reduce the number of test performed [9].…”
Section: Discussionmentioning
confidence: 99%
“…The possible explanation could be that the requesting physician ordered unnecessary tests for those patients. Inappropriate use of the laboratory has been widely documented in clinical practice (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…Although many articles were recently published on demand management, few have looked at the impact on patient outcomes. Wang et al 22 assessed strategies to reduce unnecessary testing in a coronary care unit and found that reduced testing did not have any adverse effects on outcomes but the power of the study to assess outcomes was limited. Measuring clinical outcomes is difficult as the impact of changes in laboratory testing is unlikely to be sufficiently large to produce statistically significant changes in unequivocal endpoints such as death or hospitalisation, and surrogate endpoints are therefore needed.…”
Section: Hba1cmentioning
confidence: 99%